COMMUNITY RESILLIENCE PADA PENYINTAS BENCANA ALAM DI PROVINSI YOGYAKARTA - zarina akbar; Iriani Indri Hapsari; Burhanuddin Tola (Analitika: Jurnal Magister Psikologi UMA, 2017)
This article presents the implementation of core principles and value of community resillience approach in Yogyakarta province. Model program is described in situations of community and conditions post disasters to suggest ways to foster community resilience. Community resilience encompasses individual preparedness as well as establishing a supportive social context in communities to withstand and recover from disasters. Participants were drawn from the inhabitants of Cangkringan districts Yogyakarta Province. In this research also examine the challenges of integrating model of community resillience to stimulate more disaster awareness and importance of developing for evaluation this model in society. The goal is also to see under which conditions natural disasters can be considered windows of opportunity for sustainability community resilience in society.